Australian Group on Antimicrobial Resistance Hospital-onset Staphylococcus aureus Surveillance Programme annual report, 2011 - Coombs, Geoffrey; Nimmo, G.; Pearson, J.; Collignon, P.; Bell, J.; McLaws, M.; Christiansen, K.; Turnidge, J. (2013)
In 2011, the Australian Group on Antimicrobial Resistance (AGAR) conducted a period-prevalence survey of clinical Staphylococcus aureus isolated from hospital inpatients. Twenty-nine microbiology laboratories from all states and mainland territories participated. Specimens were collected more than 48 hours post-admission. Isolates were tested by Vitek2® antimicrobial susceptibility card (AST-P612 card). Nationally, the proportion of S. aureus that were methicillin-resistant S. aureus (MRSA) was 30.3%; ranging from 19.9% in Western Australia to 36.8% in New South Wales/Australian Capital Territory. Resistance to the non-ß-lactam antimicrobials was common except for rifampicin, fusidic acid, high-level mupirocin and daptomycin. No resistance was detected for vancomycin, teicoplanin or linezolid. Antibiotic resistance in methicillin susceptible S. aureus (MSSA) was rare apart from erythromycin (13.2%) and there was no resistance to vancomycin, teicoplanin or linezolid. Inducible clindamycin resistance was the norm for erythromycin resistant, clindamycin intermediate/susceptible S. aureus in Australia with 90.6% of MRSA and 83.1% of MSSA with this phenotype having a positive double disc diffusion test (D-test). The proportion of S. aureus characterised as being healthcare-associated MRSA (HA-MRSA) was 18.2%, ranging from 4.5% in Western Australia to 28.0% in New South Wales/Australian Capital Territory. Four HA-MRSA clones were characterised and 98.8% of HA-MRSA isolates were classified as either ST22-IV [2B] (EMRSA-15) or ST239-III [3A] (Aus-2/3 EMRSA). Multiclonal community-associated MRSA (CA-MRSA) accounted for 11.7% of all S. aureus. In Australia, regional variation in resistance is due to the differential distribution of MRSA clones between regions, particularly for the major HA-MRSA clone, ST239-III [3A] (Aus-2/3 EMRSA), which is resistant to multiple non-ß-lactam antimicrobials.